2022
DOI: 10.3389/fmolb.2022.910928
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis patterns in papillary renal cell carcinoma are characterized by distinct tumor microenvironment infiltration landscapes

Abstract: Cuproptosis is a novel kind of programmed cell death that has been linked to tumor development, prognosis, and responsiveness to therapy. Nevertheless, the precise function of cuproptosis-related genes (CRGs) in the tumor microenvironment (TME) remains unknown. We characterized the genetic and transcriptional changes of CRGs in papillary renal cell carcinoma (PRCC) samples and analyzed the expression patterns in two separate cohorts. We observed that two unique cuproptosis-related subgroups and three separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the present study, we evaluated 19 CRGs and investigated their somatic mutation, CNV, differential expression level, PPI network, methylation analysis, and biological pathway in PC. The higher frequency mutation rate of CDKN2A and downregulated CNV level further con rmed that at the time of malignancy, CNV is the main type of somatic mutation in the DNA sequence (Zhang et al 2022). These results also suggested that CNV may interfere with the expression of 19 cuproptosis genes.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, we evaluated 19 CRGs and investigated their somatic mutation, CNV, differential expression level, PPI network, methylation analysis, and biological pathway in PC. The higher frequency mutation rate of CDKN2A and downregulated CNV level further con rmed that at the time of malignancy, CNV is the main type of somatic mutation in the DNA sequence (Zhang et al 2022). These results also suggested that CNV may interfere with the expression of 19 cuproptosis genes.…”
Section: Discussionmentioning
confidence: 81%
“…Accumulation of copper ions has been shown to enhance cell proliferation, growth, angiogenesis and metabolism [ 13 ]. Copper ion imbalance is an critical element in the development and occurrence of cancer [ 14 ]. A novel approach to treat cancer based on copper toxicity has been mentioned by Kahlson et al [ 15 ].…”
Section: Introductionmentioning
confidence: 99%